2017
DOI: 10.1038/srep40499
|View full text |Cite
|
Sign up to set email alerts
|

An Inert Pesticide Adjuvant Synergizes Viral Pathogenicity and Mortality in Honey Bee Larvae

Abstract: Honey bees are highly valued for their pollination services in agricultural settings, and recent declines in managed populations have caused concern. Colony losses following a major pollination event in the United States, almond pollination, have been characterized by brood mortality with specific symptoms, followed by eventual colony loss weeks later. In this study, we demonstrate that these symptoms can be produced by chronically exposing brood to both an organosilicone surfactant adjuvant (OSS) commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 70 publications
3
77
0
1
Order By: Relevance
“…It is also possible that immune system dynamics in relationship to aggression vary with the type of stressor experienced (Gregory et al 2005;Fine et al 2017); low aggression bees may be more susceptible to a pesticide, but less susceptible to a pathogen (the latter was not measured).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that immune system dynamics in relationship to aggression vary with the type of stressor experienced (Gregory et al 2005;Fine et al 2017); low aggression bees may be more susceptible to a pesticide, but less susceptible to a pathogen (the latter was not measured).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that immune system dynamics in relationship to aggression vary with the type of stressor experienced (Gregory et al 2005;Fine et al 2017); low aggression bees may be more susceptible to a pesticide, but less susceptible to a pathogen (the latter was not measured).…”
Section: Discussionmentioning
confidence: 99%
“…Additional research into the bees' response to simultaneous Varroa infestation and DWV infection proved that honey bees are able to promptly produce high immune and homeostatic response, which does not last long and is followed by downregulation of these pathways, rendering the bees susceptible to extensive virus replication [56]. Fine et al [67] reported that even inert substances in agrochemicals may also add to some negative effects on bees, including increased virus-induced mortality. Herbicides, although designed to inhibit weed growth, limit the availability of fl oral resources and adversely affect the bees` nutritional status, indirectly infl uencing the outcome of bee virus infections.…”
Section: Infestation With Varroa Destructor and Mixed Virus Infectionsmentioning
confidence: 99%